Naturally Occurring Glycosidases in Milk from Native Cattle Breeds: Activity and Consequences on Free and Protein Bound-Glycans - Sunds, Anne Vuholm; Roland, Ida Schwartz; Sundekilde, Ulrik Kræmer; Thesbjerg, Martin Nørmark; Robinson, Randall; Bunyatratchata, Apichaya; Glantz, Maria; Paulsson, Marie; Leskauskaite, Daiva; Pihlanto, Anne; Inglingstad, Ragnhild; Devold, Tove Gulbrandsen; et al. (MDPI AG, 2021)
Little is known about the extent of variation and activity of naturally occurring milk glycosidases and their potential to degrade milk glycans. A multi-omics approach was used to investigate the relationship between glycosidases and important bioactive compounds such as free oligosaccharides and O-linked glycans in bovine milk. Using 4-methylumbelliferone (4-MU) assays activities of eight indigenous glycosidases were determined, and by mass spectrometry and 1H NMR spectroscopy various substrates and metabolite products were quantified in a subset of milk samples from eight native North European cattle breeds. The results showed a clear variation in glycosidase activities among the native breeds. Interestingly, negative correlations between some glycosidases including β-galactosidase, N-acetyl-β-d-glucosaminidase, certain oligosaccharide isomers as well as O-linked glycans of κ-casein were revealed. Further, a positive correlation was found for free fucose content and α-fucosidase activity (r = 0.37, p-value < 0.001) indicating cleavage of fucosylated glycans in milk at room temperature. The results obtained suggest that milk glycosidases might partially degrade valuable glycans, which would result in lower recovery of glycans and thus represent a loss for the dairy ingredients industry if these activities are pronounced.
Keywords: natural glycosidases; oligosaccharides; O-linked glycans; principal component analysis; cattle breeds; mass spectrometry; NMR spectroscopy; natural glycosidases; oligosaccharides; O-linked glycans; principal component analysis; cattle breeds; mass spectrometry; NMR spectroscopy